FeS2-Quantum-Dot Sensitized Metal Oxide Photoelectrodes: Photoelectrochemistry and Photoinduced Absorption Spectroscopy. (17th November 2011) - Bedja, Idriss; Hagfeldt, Anders
Abstract : TiO2, ZnO nanoparticulate(-np), and ZnO-nanorod(-nr) electrodes have been modified with FeS2 (pyrite) nanoparticles. Quantum size effect is manifested by a blue shift in both absorption and photocurrent action spectra. PIA (photoinduced absorption spectroscopy), a multipurpose tool in the study of dye-sensitized solar cells, is used to study quantum-dot modified metal oxide (MO) nanostructured electrodes. The PIA spectra showed an evidence for long-lived photoinduced charge separation. Time-resolved PIA showed that recombination between electrons and holes occurs on a millisecond timescale. Incident-photon-to-current efficiencies at 400 nm are ranged between 13% and 25%. The better solar cell performance of FeS2 on ZnO-nr over ZnO-np can be ascribed to the faster, unidirectional e-transport channels through the ZnO-nr as well as the longer electron lifetimes. The lower performances of electrodes can be explained by the presence of FeS2 phases other than the photoactive pyrite phase, as evidenced from XRD study.